International Commercial Courts in the 'Modern Law of Nature': Adjudicatory Unilateralism in Special Economic Zones. (19th April 2021) - Dimitropoulos, Georgios
ABSTRACT: International commercial courts are currently proliferating from the last generation special economic zones of the Gulf region to the whole of Asia and Europe. International commercial courts are institutions of a new era of international economic law and adjudication. Zone courts, alongside the new uses of arbitration within special economic zones, may be viewed as the adjudicatory counterpart of the move towards unilateralism in international economic law. The idea is to move cases from the international to the domestic realm and overall domesticate international economic law and adjudication. The unilateral strategy to achieve this is the introduction of new courts that sit in a space between the national and the international and are based on English (common) law. However, the new system does not oblige the transferal of cases. The special economic zones-driven judicial unilateralism adds an investment attraction to the repertoire of states, as well as choices to parties. Adjudicatory unilateralism is thus consubstantially plural. The creation and proliferation of English (common) law-based special economic zones and international commercial courts is a major shift that will have deep implications for the system of international economic law and adjudication.